2009
DOI: 10.1002/ajmg.a.32827
|View full text |Cite
|
Sign up to set email alerts
|

A novel de novo 1.1 Mb duplication of 17q21.33 associated with cognitive impairment and other anomalies

Abstract: We report on a 14-year-old girl with mild cognitive impairment, deafness, and an unusual pattern of anomalies associated with a previously unreported de novo duplication of chromosome 17q21.33. The 1.1 Mb duplication was detected by Affymetrix 100K GeneChip array genome hybridization and involves the genomic region between 45,093,544 and 46,196,038 base pairs on chromosome 17 (NCBI build 36.1). The patient has microcephaly, unusual cup-shaped ears, scoliosis and other skeletal defects. Two genes involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Mutations in genes encoding proteins in the integrin α3β1-Arg signaling axis have been linked to human disorders in brain development. For example, chromosomal microdeletions involving integrinα3 and duplications of integrinα3 coding regions have been found in patients with intellectual disability (Zahir et al, 2009; Preiksaitiene et al, 2012). Likewise, microdeletions involving genes for integrin β1 (Megarbane et al, 2001; Talkowski et al, 2012), Arg (Scarbrough et al, 1988; Takano et al, 1997; Chaabouni et al, 2006), p190 (James et al, 1996; Leal et al, 2009), and Rho-family GTPases(Newey et al, 2005; Benarroch, 2007) have all been identified in cases of intellectual disability that have been associated with developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in genes encoding proteins in the integrin α3β1-Arg signaling axis have been linked to human disorders in brain development. For example, chromosomal microdeletions involving integrinα3 and duplications of integrinα3 coding regions have been found in patients with intellectual disability (Zahir et al, 2009; Preiksaitiene et al, 2012). Likewise, microdeletions involving genes for integrin β1 (Megarbane et al, 2001; Talkowski et al, 2012), Arg (Scarbrough et al, 1988; Takano et al, 1997; Chaabouni et al, 2006), p190 (James et al, 1996; Leal et al, 2009), and Rho-family GTPases(Newey et al, 2005; Benarroch, 2007) have all been identified in cases of intellectual disability that have been associated with developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously pointed out CACNA1G implication in patient phenotypes. Zahir et al [] and Preiksaitiene et al [] proposed that CACNA1G overexpression or haploinsufficiency was responsible for intellectual disability in patients harboring respectively a de novo 1.1 Mb duplication or 1.8 Mb deletion on 17q21.33. Another patient reported in the DECIPHER database (ID 255632), presenting with intellectual disability and dysmorphic features, had a de novo 1.92 Mb deletion that affected 37 genes including CACNA1G gene (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, one case with Klippel-Feil anomaly had a translocation involving chromosome band 17q23 (26), which is close to the human hemp orthologous locus at 17q21.3. In addition, several patients with unrelated skeletal abnormalities were shown to bear chromosomal aberrations involving 17q21.3 (28)(29)(30). Therefore, it would be intriguing to investigate whether human hemp expression is affected in patients with Klippel-Feil anomaly and patients with skeletal abnormalities carrying chromosomal aberrations involving 17q21.3.…”
Section: Discussionmentioning
confidence: 99%